Daily urinary urea excretion to guide intermittent hemodialysis weaning in critically ill patients. Issue 1 (December 2016) - Aniort, Julien; Ait Hssain, Ali; Pereira, Bruno; Coupez, Elisabeth; Pioche, Pierre; Leroy, Christophe; Heng, Anne; Souweine, Bertrand; Lautrette, Alexandre
Abstract Background There are no easily available markers of renal recovery to guide intermittent hemodialysis (IHD) weaning. The aim of this study was to identify markers for IHD weaning in critically ill patients with acute kidney injury (AKI). Methods We performed a retrospective single-center cohort study of patients treated with IHD for at least 7 days and four dialysis sessions for AKI between 2006 and 2011 in an intensive care unit (ICU) of a French university hospital. Blood and urinary markers were recorded on the day of the last IHD in the ICU for unweaned patients and 2 days after the last IHD for weaned patients. Factors associated with IHD weaning were identified by multiple logistic regression. The areas under the receiver operating characteristic curve (AUROC) and the characteristics of the best diagnostic thresholds were compared. Results Sixty-seven patients were analyzed, including thirty-seven IHD-weaned patients. Urine output [odds ratio (OR) 1.59, 95 % confidence interval (CI) 1.20–2.10 (per ml/kg/24 h increase);P  = 0.01] and urinary urea concentration [OR 1.29, 95 % CI 1.01–1.64 (per 10 mmol/L increase);P  = 0.04] were both associated with IHD weaning. The optimal diagnostic thresholds for IHD weaning were urine output greater than 8.5 ml/kg/24 h, urinary urea concentration greater than 148 mmol/L, and daily urea excretion greater than 1.35 mmol/kg/24 h, with accuracy of 82.1 %, 76.1 %, and 92.5 % (P  = 0.03), respectively. The AUROC of daily urinary urea excretion (0.96) was greater than the AUROC of urine output (0.86) or the AUROC of urinary urea concentration (0.83) (P  < 0.001). Conclusions A daily urinary urea excretion greater than 1.35 mmol/kg/24 h was found to be the best marker for weaning ICU patients with AKI from IHD.